Antena Vivaldi Antipodal 2-18 GHz untuk Aplikasi Direction Finding Sinyal - Latika Herda, Deri; Suryana, Joko; Agres Yudithia, Frenzi; Maria, Popy; Raiqah Luthfiah, Najla (ELECTRON Jurnal Ilmiah Teknik Elektro, 2024)
The demand for advanced direction-finding systems operating in the 2-18 GHz frequency range has surged due to their role in cellular, satellite, and military applications. This increased demand has also led to a rise in illegal transmissions within this spectrum, highlighting the need for accurate signal detection and localization. This paper discusses the design and analysis of a compact antipodal Vivaldi antenna (AVA) aimed at detecting illegal transmitters within the 2-18 GHz band. Direction-finding systems require antennas with wide bandwidth, high gain, and directional radiation patterns to meet performance criteria. The Vivaldi antenna, with its tapered slot design, offers these features, making it ideal for precise signal detection. Designed on an FR-4 substrate with a relative permittivity of 4.6, the antenna's performance was optimized using CST Microwave Studio software. The antenna was fabricated using wet etching on a copper conductor. Measurement results show that the antenna exhibits a directional radiation pattern, with a maximum gain of 10.527 dBi at 8 GHz, surpassing the simulated gain of 8.12 dBi, and an average measured gain of 5.975 dBi, exceeding the design requirement of 4 dBi. Operating effectively across a 2.7-18 GHz range, the antenna achieves a bandwidth of 15.3 GHz, fulfilling 95.625% of the specified range. Despite minor shifts in the reflection coefficient due to dielectric permittivity variations in the FR-4 substrate, the antenna demonstrates strong performance for direction-finding applications. This study highlights the AVA's potential for high-performance detection of illegal transmitters and discusses design challenges and opportunities for optimization